Solidification Processing of Metallic Alloys Under External Fields (Springer Series in Materials Science,, 2018)
This book explores the application of external physical fields to the solidification processing of metallic alloys. Leading academics from around the world present comprehensive and critical reviews on state-of-the-art research and discuss possible future directions. Major physical fields, including electromagnetic, electric, acoustic, and thermal, are considered. In addition, the most advanced synchrotron X-ray based real-time and in-situ studies and numerical modeling methodologies are reviewed and discussed, with a special emphasis on their applications to the solidification processes. Throughout, all chapters are illustrated with both historical and very recent research cases, including typical examples of in-situ studies, modeling, and simulation. This book contains essential knowledge and information suitable for a wide audience, from undergraduate and postgraduate students to academics, practicing researchers, and engineers in materials, metallurgy, and manufacturing. Presents state-of-the-art research in an important and fast-growing field Covers fundamental theory, real-time characterization, modeling, and applications Features a combination of original results and systematic review of published literature by the leading researchers in the world Represents a comprehensive reference for researchers and engineers working in materials processing.